A co-integration analysis of the price and income elasticity of energy demand - Mitchell, Travis (Central Bank of Barbados [St. Michael]BB, 2006)
Examines the price and income elasticity of Barbados' demand for energy, using a simple demand function and data spanning the period 1960 -2005.